2012
DOI: 10.1016/j.jacc.2011.08.066
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI of Inflammation in Myocardial Infarction

Abstract: Objectives The aim of this study was to explore post-MI myocardial inflammation. Background Innate immune cells are centrally involved in infarct healing and are emerging therapeutic targets in cardiovascular disease, however; clinical tools to assess their presence in tissue are scarce. Furthermore, it is currently not known if the non-ischemic remote zone recruits monocytes. Methods Acute inflammation was followed in mice with coronary ligation by 18FDG PET/MRI, FACS, PCR and histology. Results Gd-DTPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
236
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(260 citation statements)
references
References 34 publications
14
236
2
2
Order By: Relevance
“…Despite the importance of measuring the accumulation of tracers on the cellular level in animals, doing so is a challenge when using 18 F-labeled imaging agents, which generally produce extremely low radioactivity per cell and are constrained by the short decay half-life of 18 F (109.8 min) (43,44). We have devised a protocol that combines MACS, γ-counting, and flow cytometry (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of measuring the accumulation of tracers on the cellular level in animals, doing so is a challenge when using 18 F-labeled imaging agents, which generally produce extremely low radioactivity per cell and are constrained by the short decay half-life of 18 F (109.8 min) (43,44). We have devised a protocol that combines MACS, γ-counting, and flow cytometry (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous image acquisition with PET and MRI seamlessly co-registers acquired images from both modalities, thereby limiting misalignment and partial volume effects with shorter scan times (59). In addition, PET-MRI hybrid imaging permits synchronized evaluation of multiple physiologic and disease processes by incorporating complementary molecular imaging probes (60,61).…”
Section: Future Of Clinical Imaging Of Aamentioning
confidence: 99%
“…Among other things, this could be utilized as a success parameter in studies regarding cardioprotection. Other studies using PET/MRI have shown that after diet conversion of myocardial metabolism to fatty acid metabolism, the inflammatory reaction in the myocardial scar after myocardial infarction can be observed due to increased glucose utilization [14,16]; this could be used to guide new therapies to modulate infarct healing. Likewise, imaging of angiogenesis in the course of infarct healing uses special PET tracers such as αvβ3 Integrin; in the future this may result in additional applications of cardiac PET/ MRI [17].…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%